2021
DOI: 10.2147/rmhp.s338520
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hesitancy Towards COVID-19 Vaccines in State of Kuwait: An Exploratory Internet-Based Survey

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has wrought havoc upon healthcare and economic systems worldwide. COVID-19 vaccines considered a beacon of hope for normal life to return. We wished to understand the willingness of people in Kuwait to be vaccinated against COVID-19. Methods An online, exploratory, cross-sectional study was conducted on 16–18 January 2021 using a validated structured questionnaire to collect data from adults aged 18 years or ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
(171 reference statements)
3
16
0
Order By: Relevance
“… 3–10 The study also found substantial regional and residential variations in the COVID-19 vaccination hesitancy among the population. 12 , 15 Findings show that people in urban areas were less likely to experience vaccination hesitancy compared to their counterparts in the rural areas which correlates with previous studies elsewhere. 12 The reason for this could be that access to information and vaccination points is limited among rural people which could partly explain their low uptake.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“… 3–10 The study also found substantial regional and residential variations in the COVID-19 vaccination hesitancy among the population. 12 , 15 Findings show that people in urban areas were less likely to experience vaccination hesitancy compared to their counterparts in the rural areas which correlates with previous studies elsewhere. 12 The reason for this could be that access to information and vaccination points is limited among rural people which could partly explain their low uptake.…”
Section: Discussionsupporting
confidence: 70%
“… 7 , 8 Further, demographic factors such as work place, occupation, parity, age and sex/gender have also shown association with COVID-19 vaccine hesitancy. 7 , 8 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Interest in vaccination was signifi cantly higher in younger U n c o r r e c t e d people, males, those with a history of infl uenza vaccination, and health care workers. Data on vaccine safety and effi cacy, mandatory travel requirements, and government-or employer-mandated vaccination would contribute to motivation to get vaccinated (12). According to the results of the Hong Kong study published in April 2020, a total of 45.3 % of participants (out of 1,501 respondents) intended to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the next global challenge, after successfully developing a vaccine against COVID-19, will be to persuade a sufficient proportion of the inhabitants to accept vaccination, and thus mitigate the impact of the virus around the world [77,78]. It has been reported that the willingness to get vaccinated against COVID-19 in Kuwait was positively influenced by younger age, being male, having a higher education level, having been previously vaccinated against seasonal influenza, being a healthcare worker and working in the private sector [79]. Similar results were observed in a study that assessed the COVID-19 vaccine hesitancy among Ethiopian healthcare workers [80], among undergraduate students from central and southern Italy [81] and among the Chinese population [82].…”
Section: Discussionmentioning
confidence: 99%